Contested Land: Claims and Backgrounds of Clash on Bukit Duabelas National Park - Yusuf, Muhammad; Putra, Dinda Syufradian; Rohayati, Wahyu (Political Sciences Program Study, 2026)
This research aims to analyse claims in the conflict after the joint stipulation of TNBD management policy and its background. The zoning-based forest area management policy has caused multidimensional conflict between the government and the Orang Rimba. The results showed that the conflict became multidimensional because the involvement of other actors who previously had no interest in forest resources penetrated the forest area, causing the problem to become more complex. Conflicts that continue to occur are caused by policies agreed upon that do not impact those living in the area to reaccess forest resources freely. In addition, the contradiction between formal regulations and local customary law is also a cause of conflict. The policies implemented are considered inappropriate to the existing conditions because they do not feel the existence of indigenous peoples living in the area. Therefore, in forest management with regions with specificities, such as indigenous peoples, there needs to be a comprehensive policy accompanied by a deep understanding of local values. Differences in understanding the policy context are the root cause of conflict.